HUBUNGAN MOTIVASI BELAJAR DAN KECERDASAN INTELEKTUAL DENGAN HASIL BELAJAR PAI DI SD NEGERI WILAYAH 5 SAENTIS DELI SERDANG - Nurliana Pohan (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This study aims to examine the relationship between learning motivation andintellectual intelligence with learning outcomes both individually and together. The population of this study amounted to 272 students, a sample of 98 people. Learning motivation data using a Likert scale questionnaire. The intellectual intelligence of students is tested, learning outcomes are obtained through report cards. The results of the first hypothesis analysis are 15.5%. The second hypothesis is 10.04%. The third hypothesis is 27.46%. the remaining 72.54% is influenced by other variables not measured in this study.